(untitled) (Environment & Health, 2015)
Objective. We substantiated scientifically the principles of the use of gender approaches in the formation of the health protection programs for children and youth. Methods. Analytical, clinical8physiological, social, psychological, statistical methods were used in the study. Results. We established that social8psychological sex of the patient (gender) is the main item for the preventive section of health protection system (in particular, for health promotion). At the same time the biological sex is important for the therapeutic section. We determined that the preventive programs trained on health promotion and disease prevention (the programs in public health) should be subjected to a gender analysis. The sanitary8educational and ecologic8educational programs for children and youth should pass a gender assessment. Performance of gender and sexual education is necessary for the formation of the adequate psychological sex of a child. Gender (social sex) as well as age and biological sex has to be a stratifica8 tion category in the data analysis of the factors of the formation of social peculiarities of the adolescents’ health and lifestyle: keeping the health protection behavior, cancellation from the unhealthy habits, ecologic consciousness, etc.